Pointing to Azimuths and Elevations of Targets: Blind and Blindfolded-Sighted. (February 2014) - Wnuczko, Marta; Kennedy, John M
Three groups of observers pointed to target circles in a path on the ground, in two parallel rows. Participants in one group viewed the circles and then pointed blindfolded. Those in a second group were blindfolded and then touched the circles with a stick while walking past them. Volunteers in the third group were blind adults, a diverse group, who also used a stick to detect the circles. For all three groups, as distance to the circles increased, pointing azimuths shrank and elevations increased. We suggest that directions to targets on major environmental surfaces may be appreciated similarly by the blind and sighted. We challenge the assumption that the principle of convergence to the horizon, available through vision because of the way in which visual angle decreases on the retina, is not available through touch.